Tolerancia a suelos ácidos en poblaciones tropicales de maíz del CIMMYT - Ceballos, H.; Pandey, S.; Knapp, E.B.; Duque, J.V. (1994)
Tropical corn populations tolerant to acid soils. Currently, five tropical maize populations from CIMMYT are being bred for tolerance to acid soils through a full-sib recurrent selection scheme. Three cycles of selection from each population were evaluated in a split-plot design, with a varied number of replications under five environments (with normal soils, and the remaining four with varying degrees of soil stress). The observed genetic gains from these populations were highly significant: 4.72 % per cycle at all environments, 4.90% per cycle in acid soil environments (LSA), and 4.21 % per cycle for the normal soil location (LNA). The results suggest adequate genetic variability and high heritability for tolerance to soil acidity. In comparative trials, these populations yielded anaverage of 2.29 and 6.25 t/ha in the three LSA and two LNA environments, respectively. Under the same environments, the controls used (Tuxpeño, Pool 26 and Suwan-1) yielded anaverage of 1.28 and 5.56 t/ha.